2014
DOI: 10.1186/0717-6287-47-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of berberine in ameliorating Schistosoma mansoni-induced hepatic injury in mice

Abstract: BackgroundSchistosomiasis is caused by helminth parasites of the genus Schistosoma. Berberine chloride (BER), an isoquinoline alkaloid, has been used in vivo for its antiparasitic, antioxidant and hepatoprotective properties. In this study, the protective effect of BER and praziquantel has been compared for the extent of schistosomiasis-induced oxidative stress in hepatic tissue of mice.ResultsS. mansoni was able to induce inflammation and injury to the liver, evidenced (i) by an increase in inflammatory cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 34 publications
6
35
0
Order By: Relevance
“…This may be due to necrosis, with increased leakage of these enzymes from hepatocytes to the blood and replacement of normal liver tissue with granuloma lesions around entrapped schistosome eggs. Our data are in accordance with those of other authors [31, 40] who reported decreased AST and ALT levels in liver homogenates of S. mansoni -infected mice with concomitant increases in serum transaminases. The increase in enzyme activity is attributed to the irritation of liver cells by toxins or metabolic products of growing worms, adult worms and eggs [41].…”
Section: Discussionsupporting
confidence: 94%
“…This may be due to necrosis, with increased leakage of these enzymes from hepatocytes to the blood and replacement of normal liver tissue with granuloma lesions around entrapped schistosome eggs. Our data are in accordance with those of other authors [31, 40] who reported decreased AST and ALT levels in liver homogenates of S. mansoni -infected mice with concomitant increases in serum transaminases. The increase in enzyme activity is attributed to the irritation of liver cells by toxins or metabolic products of growing worms, adult worms and eggs [41].…”
Section: Discussionsupporting
confidence: 94%
“…Several studies show that berberine via its antioxidant activity exerts beneficial effects on Schistosoma mansoni ‐induced organ toxicity in splenic (Al‐Quraishy et al ., ), hepatic (Dkhil, ), renal and testicular tissues of mice (Dkhil et al , ).…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…BBR is widely distributed and inexpensive, so clinical and academic institutions conducted extensive research on it. In recent years, with the in‐depth study of BBR, BBR has been found to have a wide range of pharmacological effects (Imenshahidi & Hosseinzadeh, ), including hypoglycemic (Pang et al, ), hypolipidemic (Li, Jiang, & Kong, ), hypotension (Guo, Sun, Zhang, & Zhang, ), antidepressant (Sun et al, ), anti‐inflammatory (Liu, Yin, Ding, Wang, & Wang, ), antiviral (Shin et al, ), antibacterial (Peng et al, ), and antiparasitic (Dkhil, ), and other pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%